Strategic Compromise, Policy Bundling and Interest Group Power - Luna Bellani; Vigile Marie Fabella; Francesco Scervini (Institute of Labor Economics (IZA), 2020)
Policy reforms are often multifaceted. In the rent-seeking literature policies are usually taken as one-dimensional. This paper models policy formation using a political contest with endogenous policy proposals containing two dimensions. The two dimensions provide an opportunity to trade off one policy over another to make the lobbying opposition less aggressive. In a first stage, the Government proposes a reform over the two policies, and in a second stage engages in a contest with an Interest Group over the enactment of the proposed reform. As a result, the Government makes a compromise, under-proposing in the policy the Interest Group opposes and over-proposing in the policy the Interest Group desires. Effectively, there will be strategic bundling of desired policies with undesired ones in an attempt to increase enactment probability and overall utility.
Keywords: D72; D86; H4; 330; contest; political reforms; lobbies